2022
DOI: 10.1007/s12193-022-00392-4
|View full text |Cite
|
Sign up to set email alerts
|

A SLAM-based augmented reality app for the assessment of spatial short-term memory using visual and auditory stimuli

Abstract: A SLAM-based Augmented Reality (AR) app has been designed, developed, and validated to assess spatial short-term memory. Our app can be used with visual and auditory stimuli and can run on mobile devices. It can be used in any indoor environment. The anchors and data of the app are persistently stored in the cloud. As an authoring tool, the type of stimulus, its number, and specific positions in the real environment can be customized for each session. A study involving 48 participants was carried out to analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…There are previous works on the use of AR for the assessment of spatial memory. Most of these works were presented by our research group [1], [35]- [39]. The first works [35], [36] developed an AR application that used images as targets.…”
Section: Computer-assessed Spatial Memorymentioning
confidence: 99%
See 2 more Smart Citations
“…There are previous works on the use of AR for the assessment of spatial memory. Most of these works were presented by our research group [1], [35]- [39]. The first works [35], [36] developed an AR application that used images as targets.…”
Section: Computer-assessed Spatial Memorymentioning
confidence: 99%
“…The study concluded that the distance estimations were more accurate when displaying a grid but that object location memory performance was worse when displaying a grid. Auditory stimuli have also been studied for the assessment of spatial memory [39]. This work presented an AR application that included visual and auditory stimuli for the assessment of spatial memory.…”
Section: Computer-assessed Spatial Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…SLAM has been widely used in various fields, such as indoor autonomous navigation (Wen et al, 2021), virtual reality (VR) (Jiang et al, 2022), and augmented reality (AR) (Juan et al, 2022). Conventional VSLAM typically relies on point features to track the movements of agents and build maps, as this approach is simple and effective.…”
Section: Introductionmentioning
confidence: 99%
“…SLAM has been widely used in various fields, such as indoor autonomous navigation (Wen et al, 2021), virtual reality (VR) (Jiang et al, 2022), and augmented reality (AR) (Juan et al, 2022).…”
mentioning
confidence: 99%